PENGARUH JUMLAH PENDUDUK DAN PERTUMBUHAN EKONOMI TERHADAP PENDAPATAN ASLI DAERAH (PAD) KABUPATEN/KOTA DI WILAYAH KALIMANTAN - B01109109, DANTI B01109109 ANGGREINI (Jurnal Pembangunan dan Pemerataan, 2016)
This research is titled â€œThe Influence Of Population Size And Economic Growth On Local Original Revenue Of Regencies And Municipalities In Kalimantan Regionâ€. This research aims to â€œknowing and analyzing the influence of population size and economic growth on local original revenue of regencies and municipalities in Kalimantan regionâ€. Simple linear regression method is applied to analyze panel data which is obtained from the publications of the Indonesia Statistics and the publications of the Diractorate General of Fiscal Balance (DJPK). From data estimation and analysis, it can be explained that the number of population has positive and significant influence on local original revenue (9.053887 > 1.970956). While, economic growth also positively and significantly (2.992804 > 1.970956) influences local original revenue of regencies and municipalities in Kalimantan Region. This estimation has level of confident at 95%. For F test, it can be conclude that population size and economic growth also influences local original revenue of regencies and municipalities in Kalimantan Region. This test has level of confident at 95% with strong linear relationship as indicated by result of R2 which is 0.921072. It means that population size and economic growth contributes towards the increase of local original revenue of regencies and municipalities in Kalimantan Region because the value of R2 was close to 1. Keywords : Population Size, Economic Growth , Local Original Revenue (PAD).